Rhodium‐Catalyzed Regioselective Ortho C−H Olefination of 2‐Arylindoles via NH‐Indole‐Directed C−H Bond Cleavage. Issue 5 (18th January 2018) - Han, Qingshuai; Guo, Xiemin; Tang, Ziyuan; Su, Lv; Yao, Zizhu; Zhang, Xiaofeng; Lin, Shen; Xiang, Shengchang; Huang, Qiufeng
Abstract: In the past decades, C−H oxidative olefination of indole at C‐2, C‐3, C‐4 and C‐7 positions was well addressed. We report here a rhodium‐catalyzed NH‐indole‐directed ortho C−H bond olefination of 2‐arylindoles. This cross‐dehydrogenative‐coupling proved to be broad in substrate scope, tolerating a variety of functional groups. The synthesis of 6 H ‐isoindolo[2, 1‐α]indoles via rhodium‐catalyzed ortho C−H olefination and subsequent intramolecular aza‐Michael reaction of 2‐arylindoles was also demonstrated. Abstract :